PENERAPAN METODE MUROJA’AH DAN MUDARASAH DALAM MENGKOKOHKAN HAFALAN SANTRI - Khoirun Nisa, Lulu’; Ishthifaiyah, Ulumil; Mufa’izah, Mufa’izah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Muraja'ah is a method that helps memorizers of the Koran to maintain their memorization. The Hikmatun Najiyah Islamic boarding school is one of the educational institutions which includes a tahfidzul Qur'an program. The boarding school applies muraja'ah and mudarasah methods to help students maintain their memorization. The muraja'ah and mudarasah methods at the Hikmatun Najiyah Islamic boarding school are very systematic in the sense that this method is carried out by students repeating their memorization and being listened to by their tahfidz teacher. In this research, the researcher used a descriptive qualitative approach because the researcher only analyzed the application of the muraja'ah and mudarasah methods in strengthening students' memorization. This research describes the techniques in the muraja'ah and mudarasah methods. In general, this method can be done individually or together, you can listen to each other's memorization with friends or listen to your own memorization. This method has been proven to be very effective in maintaining memorization of the Al-Qur'an. So, it is hoped that all memorizers of the Al-Qur'an will be able to apply the muraja'ah and mudarasah methods even though later the students will have left the Islamic boarding school and have memorized their memorization.